Eficiência de Utilização e de Aquisição ao Fósforo por Cultivares de Aveia-branca - Manica, Jonas (2017)
Genotypes of white oats with higher nutritional efficiency than phosphorus (P) produce more grains, with less applied amount of phosphate fertilizers, favoring agricultural production in soils with low available nutrient level. The objective of this work was to verify if there is intraspecific variability in oats regarding the nutritional efficiency of P. Eight cultivars of white oats and three levels of availability of P: low (0.66 - 3.73 mg / dm3) , medium (3.8 - 7.8 mg / dm3) and high (7.8 - 11.4 mg / dm3), of a Red Clay Oxisol. The experiment was carried out in an agricultural greenhouse in the year 2015. The experimental units were plastic vessels. At physiological maturation, the number of tillers and grains, the dry mass and the P concentration of the aerial part (stem, leaves, grains) and of the root, the mass of a thousand grains and of the grains, the volume, the area and the diameter of the root system. The cultivars with higher nutritional efficiency were distinguished by the higher efficiency of phosphorus use (EUP) and this was due to the accumulation of P in the aerial part (mainly the grains), in relation to the root system, allowing greater mass of grains. The cultivars that were efficient in relation to P were Barbarasul and Ouro. On the other hand, FAEM 007, URS 21, Farroupilha, Afrodite and FAPA Slava are inefficient. These two last cultivars together with Taura are not responsive to phosphate fertilization.